2023
DOI: 10.1093/ije/dyad045
|View full text |Cite
|
Sign up to set email alerts
|

Associations of periconceptional oral contraceptive use with pregnancy complications and adverse birth outcomes

Abstract: Background Periconceptional use of oral contraceptives (OCs) has been reported to increase risks of pregnancy complications and adverse birth outcomes, but risks are suggested to differ depending on the timing of discontinuation, amount of oestrogen and progestin content. Methods Prospective cohort study among 6470 pregnancies included in the PRegnancy and Infant DEvelopment (PRIDE) Study in 2012–19. Exposure was defined as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…When used for long periods, it can cause detrimental health symptoms [32]. The hormones estrogen and progesterone can facilitate sodium retention in the secretion, which increases the activity of the plasma in the excretion of angiotensin, which can improve the natural pressure [65]. Hormonal contraceptives are not caused by endometrial dysfunction, but they cause increased homocysteine levels in the blood, abnormal fatty blood glands and excess weight gain.…”
Section: Crosssectionalmentioning
confidence: 99%
“…When used for long periods, it can cause detrimental health symptoms [32]. The hormones estrogen and progesterone can facilitate sodium retention in the secretion, which increases the activity of the plasma in the excretion of angiotensin, which can improve the natural pressure [65]. Hormonal contraceptives are not caused by endometrial dysfunction, but they cause increased homocysteine levels in the blood, abnormal fatty blood glands and excess weight gain.…”
Section: Crosssectionalmentioning
confidence: 99%
“…A recent large prospective cohort study showed that periconceptual OCP use (within 12 months) was associated with an increased risk of preterm birth, low birth weight, and PE (RR: 1.38, 95% CI: 0.99–1.93) [ 154 ]. The increased risk of PE was strongest when the OCP was stopped within 3 months of pregnancy.…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%
“…Pregnancy outcomes may yield a more temporally adjacent context of the vascular milieu. OCP use within the past 12 months is associated with adverse pregnancy outcomes, where those who used OCP within 12 months of conception had elevated relative risk of pre‐eclampsia, pre‐term birth, and low birthweight compared with those who did not (Schreuder et al., 2023 ). As Kirby et al.…”
mentioning
confidence: 99%